2010
DOI: 10.1002/mabi.201000388
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Mucoadhesion and Mucoadhesive Polymers

Abstract: Mucoadhesion is the ability of materials to adhere to mucosal membranes in the human body and provide a temporary retention. This property has been widely used to develop polymeric dosage forms for buccal, oral, nasal, ocular and vaginal drug delivery. Excellent mucoadhesive properties are typical for hydrophilic polymers possessing charged groups and/or non-ionic functional groups capable of forming hydrogen bonds with mucosal surfaces. This feature article considers recent advances in the study of mucoadhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
421
1
9

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 505 publications
(465 citation statements)
references
References 107 publications
4
421
1
9
Order By: Relevance
“…Charged polymers such as SA demonstrate higher adhesion than non-ionic polymers (e.g. HPMC), because of their ability to form a strong electrostatic interaction with the charged surface of mucin [20]. The use of composite polymeric systems can be adopted to enhance the functional properties of a polymeric dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…Charged polymers such as SA demonstrate higher adhesion than non-ionic polymers (e.g. HPMC), because of their ability to form a strong electrostatic interaction with the charged surface of mucin [20]. The use of composite polymeric systems can be adopted to enhance the functional properties of a polymeric dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that displacement is observed in the absence of mucin would indicated that the use of is able to recover some of the mucoadhesive properties of the mucoadhesive polymers included within the formations, and although known to show less biophysical properties as compared to native mucin, this purified mucin has less batch-to-batch variation and hence provides better reproducibility in measuring mucoadhesive force 61 .…”
Section: In-vitro Mucoadhesionmentioning
confidence: 99%
“…Finally, the research 80 conducted to date on mucosa-mimetic materials will be summarised and discussed. Previous reviews have described the variety of mucoadhesive materials discovered (Bernkop-Schnürch and Greimel, 2005;Khutoryanskiy, 2011;Sosnik et al, 2014), so this will not be covered herein.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some sulfated sugars have been identified at the terminus of the oligosaccharides in mucins, primarily those mucins in the colon and respiratory tract, which provides another possible site of electrostatic 130 interaction (Thomsson et al, 2002). The pKa of the acidic groups in mucin is between 1 and 2.6 (Khutoryanskiy, 2011), and as a result, mucin carries a net negative charge at pHs above this (Bansil and Turner, 2006). It is important to note, therefore, that the degree of ionisation of the mucin oligosaccharides will greatly decrease as the pH approaches pH 1, as in the stomach.…”
mentioning
confidence: 99%
See 1 more Smart Citation